2017
DOI: 10.1162/comj_a_00396
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Spatial Sound Phenomena Created by the Icosahedral Loudspeaker

Abstract: The icosahedral loudspeaker (IKO) is able to project strongly focused sound beams into arbitrary directions. Incorporating artistic experience and psychoacoustic research, this article presents three listening experiments that provide evidence for a common, intersubjective perception of spatial sonic phenomena created by the IKO. The experiments are designed on the basis of a hierarchical model of spatiosonic phenomena that exhibit increasing complexity, ranging from a single static sonic object to combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…Geometry and reverberation time of the auralized rooms are based on two rooms at our institute, namely the IEM CUBE, a 10.3 m × 12 m × 4.8 m large room with T 60 = 700 ms, and the IEM Lecture Room, 7.6 m × 6.8 m × 3 m with T 60 = 570 ms. Both rooms were chosen as they are typical venues for concerts or experiments with the IKO as a variable-directivity source [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…Geometry and reverberation time of the auralized rooms are based on two rooms at our institute, namely the IEM CUBE, a 10.3 m × 12 m × 4.8 m large room with T 60 = 700 ms, and the IEM Lecture Room, 7.6 m × 6.8 m × 3 m with T 60 = 570 ms. Both rooms were chosen as they are typical venues for concerts or experiments with the IKO as a variable-directivity source [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…The studies in [14,15] extended the previous listening experiments towards simple time-varying beam directions, such as from the left to the right, front/back or circles.…”
Section: Moving Auditory Objectsmentioning
confidence: 78%
“…The maximum distance of auditory objects created by the IKO is strongly signaldependent. Experiments in [14] showed that the auditory distance of pink noise bursts decreased for shorter fade-in times, while the fade-out time had no influence, cf. Fig.…”
Section: Static Auditory Objectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laitinen [21] and Wendt [22] present experiments that use compact spherical beamformer arrays to vary distance impressions by crossfading between direct and indirect, rather diffuse sound reinforcement. In previous studies [23][24][25][26], we were able to show the basic characteristics of static and dynamic beamforming in various experiments using stationary and transient sounds. In a performance situation, a quarter-circle arrangement of reflectors is often employed to support a robust and detailed spatialization throughout the audience area [27], cf.…”
Section: Introductionmentioning
confidence: 99%